If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -3x + 2xy + -1y = 0 Reorder the terms: -3x + 2xy + 4y + -1y = 0 Combine like terms: 4y + -1y = 3y -3x + 2xy + 3y = 0 Solving -3x + 2xy + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -3x + 2xy + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 -3x + 2xy + 0 = 0 + -3y -3x + 2xy = 0 + -3y Remove the zero: -3x + 2xy = -3y Combine like terms: -3y + 3y = 0 -3x + 2xy + 3y = 0 The solution to this equation could not be determined.
| x+31=39 | | 6x+18-27=15 | | -2xy+3xy-x+3xy= | | (10x+6/2)-(4x-8/9)=(8x-8/3) | | 4x+3y-x+3xy= | | 2x+5x=1 | | 5(y-2)=25 | | x+x+x=x+6 | | m+24=33 | | 3xy+2x-3y+7= | | 7-2n=3n-38 | | 10x+6/2-4x-8/9=8x-8/3 | | 2(7x-1)=96 | | 4x-x+3y-y= | | -7(6v+5)=91 | | -6a+5(1-2a)=101 | | -10x+3y-4xy+5= | | 2k^3-36k^2=162k | | -3x+5y+3+3x-5y= | | -45=3n+9 | | (x-(2+3i))(x-(2-3i))=0 | | -5+7x-2+3x+y-8y+6= | | 10r+8=-182 | | -3xy+3xy= | | 2x+2=-2x+6 | | 2x+2=x-1 | | 5z/8=85 | | -9=x-2 | | -6(1-3x)-5x=85 | | 25x+y=13x-y | | -2+5(4n+7)=173 | | -11y^2-27=0 |